Model Pembelajaran Rally Coach untuk Meningkatkan Kemampuan Berpikir Analitis, Keterampilan Komunikasi Matematis, dan Penguasaan Konsep Matematika Siswa [Rally Coach Learning Model to Improve Students' Analytical Thinking Ability, Mathematical Communication Skills, and Mastery of Mathematical Concepts] - Harianja, Joko Krismanto (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2022)
The aim of this research is to determine the differences in analytical thinking, mathematical communication skill and the conceptual mastery between the 7th-grade students who implement the rally coach learning model and those students who do not in the classroom. This research was conducted with nineteen participants for each class. This is a quantitative research using the weak experiment method with a static-group pre-test and post-test design. The instruments used were rubrics and test questions that had been tested for their validity and reliability. The n-gain value obtained was then tested to determine the differences between the two classes using the Mann-Whitney test. Analytical thinking hypothesis test results show the acquisition of the asymp. sig (2-tailed) = 0.005; mathematical communication skill with the asymp. sig (2-tailed) = 0,000; hypothesis testing of the post-test results of the conceptual mastery with the asymp. sig (2-tailed) = 0.002 and the n-gain test obtained the asymp. sig (2-tailed)iT which is less than 0.05. From the results of these tests, it can be concluded that there are differences in the students’ analytical thinking, mathematical communication skill and the conceptual mastery in the control and experimental classes.